Methods of cultivating good habits and removing bad characteristics of the Qura'an perspective - Dianti Yuniar; Deden Badrusalam; Cepi Nurzaman; Mastuhi Mastuhi (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research is to analyze the method of cultivating good habits and removing bad characters from the perspective of the Qur'an. The research method used is library research, which examines and collects data from various literatures that are related to the discussion of the problem. In this study, researchers used two types of data, namely primary and secondary data, and secondary data sources, namely data in the form of related documents. The results of the study show that based on the various interpretations above, it is clear what is meant by QS Al Hajj verse 77: an order to get used to worship (represented by the words bowing and prostration) and also to do good deeds so that we get good luck in the afterlife. These habits should be introduced and ingrained as early as possible. In Islam, even though children who have not yet reached puberty are ordered to get used to worship, such as praying, the goal is for them to become accustomed to it until they are adults. Like someone who wants to be great at playing football, for example, it's impossible to be great at an adult age. The greatest baseball player began practicing as a child and has continued to this day. worship and good habits Begin early and instill it in your children.Of course, there are stages. starting by setting an example for toddlers. Seeing us worship, toddlers usually join in too. Then invite them without any coercion. Until the invitation with sanctions for children about to go to bed.